Correlation between folic acid and sulfas ferrosus supplementation during antenatal care and low birth weight at General Hospital Jombang, Indonesia - Mochamad Ma'roef; Bayu Hendrawan (AOSIS, 2019)
Antenatal care is a service provided by healthcare professionals for identifying health conditions among pregnant mothers. This study aimed to identify the correlation between Supplementation Folic Acid and Sulfas Ferrosus during Antenatal Care and Low Birth Weight (LBW) at General Hospital Jombang, Jombang, East Java. Observational analytic design was used in this study with case control. Simple random sampling was chosen in this study. The data was analyzed using chi-square test if p (0.000) < (0.05). According to chi-square test, the results showed a significance level of p (0.000) < (0.05). Significant correlation was obtained from the result and depicted on contingency coefficient value reaching (0.626) with OR 0.11 (95%CI:0.02-0.65). It can be concluded that there is a significant correlation between supplementation Folic Acid and Ferrous Sulfas during Antenatal Care and Low Birth Weight (LBW).